Coordinated DEI Political Attacks in President Trump’s Executive Orders through the Lens of Critical Theory: Libraries Deconstructing Dysfunctional Political Rhetoric to Further Social Justice - Bharat Mehra (The Political Librarian, 2025)
This article examines the impact of President Trump’s executive orders, selected and analyzed through a lens of critical theory, on the representation of diversity, equity, and inclusion (DEI) initiatives. It calls for strategic intervention by libraries to deconstruct the underlying political rhetoric of these executive orders, enabling their publics to resist his dysfunctional acts of aggression in the dismantling of American democracy. The goal is to integrate critical theory application to promote social justice in libraries as resistance to actualize fairness, justice, equity, empowerment, change agency, and community building in response to the troublesome political times created via a conscious and/or unconscious coercion/manipulation of the American people and the democratic process. The critical discourse reveals a disturbing resemblance between the contemporary political populism in the United States and the Depression-era conditions in Weimar, Germany, during the prewar twentieth century. The explanatory discourse resonates with truth and signals possibly tragic consequences if it remains unheeded.
Keywords: DEI; executive orders; critical theory; political attacks; President Trump